Art and Worship - Irvine, Christopher (Book collections on Project MUSE., 2002)
"Art and Worship explores the relationship between religion and the visual arts and offers advice on how to commission works of art, how to place them, and how to hold art exhibitions in church."--BOOK JACKET.